THU0711-HPR COMPARISON OF FEMALE SEXUAL FUNCTION INDEX IN PATIENTS WITH RHEUMATOID AND PSORIATIC ARTHRITIS AND HEALTHY CONTROLS. (June 2019) - Boone, Denise; Ronson, Ashley; Karsh, Jacob
Abstract : Background: Alteration in sexual functioning is not well understood in rheumatoid arthritis (RA) and psoriatic arthritis (PsA). A review of the limited current literature suggests that decreased sexual function in female RA patients is common (Zhang et al., 2018). Although RA and PsA differ in presentation and patient experience, literature regarding sexual health of female PsA patients is lacking. The Female Sexual Function Index (FSFI) is a validated and reliable self-reporting tool to assess sexual function in women within six domains: desire, subjective arousal, lubrication, orgasm, satisfaction, and pain (Rosen, et al., 2000). Objectives: The purpose of this study was to identify and compare the FSFI of three female populations: RA, PsA, and healthy individuals. Methods: Convenience sampling was used for this descriptive correlational study to recruit 50 female RA patients, 33 female PsA patients, and 25 healthy females for the control group between June to September 2018. Data collection was obtained using questionnaires and a review of the medical record including demographic characteristics, the validated FSFI, medication history, pain score, patient global, Health Assessment Questionnaire (HAQ), and laboratory data. Data was analyzed using ANOVA test with Tukey's post-hoc to determine if any differences exist for FSFI scores based on diagnosis. Analysis was run twice, initially for all participants, and secondly removing the participants who reported not having had sex within the last month. Results: The mean age of the RA patients was 53.1 ±11.8, PsA patients was 51.6 ± 13.7, and healthy controls was 37.4 ± 10.4. Controls were significantly younger than RA (p <.001) and PsA patients (p =.002). Data including all participants: Based on the total sexual functioning cutoff score of 26.55, 68% of RA female patients (34/50), 67% of PsA females patients (22/33), and 44% of healthy controls (11/25) met the criteria for sexual dysfunction. Data excluding participants who reported not having had sex in the past month: Controls had significantly higher FSFI scores than the RA patients across all six domains (p≤0.001) and the overall score (p<0.001). Controls had significantly higher FSFI scores than the PsA patients across four of the six domains (p≤0.026) and the overall score (p=0.008). There were no statistically significant differences between the RA and PsA group. Conclusion: These findings demonstrate that decreased sexual functioning is more common in patients with RA and PsA when compared to a control group. All female patients with RA and PsA should be screened for sexual dysfunction. References: [1] Rosen, R, . Brown, C., Heiman, J., Leiblum, S., Meston, C., Shabsigh, R., Ferguson, D., & D'Agostino, R. (2000). The Female Sexual Function Index (FSFI): A multidimensional self-report instrument for the assessment of female sexual function. Journal of Sex &Marital Therapy, 26(2), 191-208. doi: 10.1080/009262300278597 [2] Zhang, Q., Zhou, C., Chen, H., Zhao, Q., Li, L., Cui, Y., & Shen, B. (2018). Rheumatoid arthritis is associated with negatively variable impacts on domains of female sexual function: Evidence from a systematic review and meta-analysis. Psychology, Health & Medicine, 23(1), 114-125. doi: 10.1080/13548506.2017.1338738 Disclosure of Interests: None declared